2018
DOI: 10.5114/wo.2018.73874
|View full text |Cite
|
Sign up to set email alerts
|

The role of hypoxia in shaping the recruitment of proangiogenic and immunosuppressive cells in the tumor microenvironment

Abstract: Hypoxia characterizes growing tumors and contributes significantly to their aggressiveness. Hypoxia-inducible factors (HIFs 1 and 2) are stabilized and act differentially as transcription factors on tumor growth and are responsible for important cancer hallmarks such as pathologic angiogenesis, cellular proliferation, apoptosis, differentiation and genetic instability as well as affecting tumor metabolism, tumor immune responses, invasion and metastasis. Taking into account the tumor tissue as a whole and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…In the hypoxic TME, VEGF is thought to be the dominant chemoattractant for MDSCs, as it was shown that, both in mice and in non-small cell lung cancer (NSCLC) patients, hypoxia upregulates its expression and aids in MDSC accumulation [36]. This process of VEGF-mediated attraction to the TME is possible by means of VEGFR expression on MDSCs [37]. Primary tumor clusters can potentially gather MDSCs from the BM by releasing exosomes.…”
Section: Accumulation Of Mdscs To Tumor Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hypoxic TME, VEGF is thought to be the dominant chemoattractant for MDSCs, as it was shown that, both in mice and in non-small cell lung cancer (NSCLC) patients, hypoxia upregulates its expression and aids in MDSC accumulation [36]. This process of VEGF-mediated attraction to the TME is possible by means of VEGFR expression on MDSCs [37]. Primary tumor clusters can potentially gather MDSCs from the BM by releasing exosomes.…”
Section: Accumulation Of Mdscs To Tumor Sitesmentioning
confidence: 99%
“…The most common and well-studied mechanism of MDSC-mediated angiogenesis is the production of VEGF [36]. The VEGF family of proteins consists of VEGF-A, -B, and -C [37,58]. MDSCs exploit the abundance of VEGF in the TME, and via the tyrosine kinase receptor VEGFR, they are able to initiate a signaling cascade implicating JAK2/STAT3, resulting in the production of even more angiogenic molecules [59,60].…”
Section: The Vegf/vegfr Angiogenic Pathwaymentioning
confidence: 99%
“…Hypoxia is a common phenomenon in the tumor microenvironment (47)(48)(49). Previous studies have revealed that tumor hypoxia alters the composition and activity of tumor-associated immune cells, and that numerous immune cells with immunosuppressive activities are recruited to tumor tissues to form the immunosuppressive microenvironment (18,50,51). Under hypoxic conditions, tumor cells and macrophages secrete a variety of cytokines and chemokines, including C-C motif chemokine (CCL)22, CCL28 and IL-10, which results in the recruitment of CD4 + CD25 + FOXP3 + Tregs from peripheral blood to inhibit T cell-mediated antitumor responses (18,52,53).…”
Section: Hypoxia-induced Recruitment Of Immunosuppressive Cells and Rmentioning
confidence: 99%
“…The tumor microenvironment stimulates MDSCs also by other factors induced by local hypoxia and low pH ( 52 , 53 ). One of them is hypoxia-inducible factor (HIF).…”
Section: Myeloid-derived Suppressor Cells (Mdscs)mentioning
confidence: 99%